Employee Engagement sebagai Mediator antara Kepemimpinan dan Work-Life Balance terhadap Kinerja Pegawai: Studi pada Badan Kepegawaian Daerah Provinsi Maluku - Asmirani Tomia; Stanislaus Kostka Ohoiwutun; Mike J. Rolobessy (MAN 4 Kota Pekanbaru, 2025)
This research is conducted to examine how leadership and work-life balance influence employee performance through the mediating role of employee engagement at the Regional Personnel Agency of Maluku Province. The study employs a descriptive-quantitative method with a causal correlation design, indicating that the independent variables are hypothesized to have causal effects on the dependent variable. The research population includes all 144 employees of the Regional Personnel Agency of Maluku Province. Sampling was determined using the Isaac and Michael table, resulting in 100 respondents at a 95% confidence level, selected through simple random sampling using a lottery technique. Data were analyzed using path analysis. The findings reveal that (1) leadership positively and significantly affects employee engagement, (2) work-life balance positively and significantly affects employee engagement, (3) employee engagement positively and significantly affects performance, (4) leadership does not directly affect employee performance significantly, (5) work-life balance does not directly affect performance significantly, (6) leadership positively and significantly influences performance through employee engagement, and (7) work-life balance positively and significantly influences performance through employee engagement.